Identification of Fusarium head blight resistant sources in wheat under artificially inoculated condition - KUMAR, AKSHAY; AGGARWAL, H M; M S, RASHMI GURJAR; PRASAD, VINOD LAKSHMAN; SAHARAN, M S (The Indian Journal of Agricultural Sciences, 2021)
A set comprising 164 wheat genotypes were evaluated for Fusarium head blight (FHB) resistance under artificially inoculated conditions during 2019-20 at ICAR-IARI, New Delhi. Five spikes per plant of each genotype were inoculated with cotton web technique with Fusarium graminearum during mid anthesis stage. Scoring of disease data (percent spike and spikelet infection) was done after 7, 14 and 21 days of inoculation for calculating the Area Under Disease Progress Curve (AUPDC). No genotype was found immune, resistant and moderately resistant on the basis of per cent spike infection. On the basis of % spikelet infection recorded after 7 days of inoculation, 11 genotypes, viz. UP 3016, HI 1624, HS 668, DBW 290, HD 3331, K 1317, HD 3377, MACS 6747, HD 2864, NIDW 1149 (durum) and MACS 4087 (durum) were free from disease. On the basis of disease grade based on spikelet data recorded after 21 days of inoculation, only two genotypes, viz. HI 1636 and HD 3377 were having disease score up to 2 (moderately resistant). On the basis of categorization of varieties based on AUDPC values, only three wheat genotypes were grouped between 101-200 group (HD 3377, NIDW 1149 (durum) and HI 1612). In rest of the genotypes, AUDPC values were more than 200 while maximum AUDPC value of 900 was obtained in highly susceptible variety, Sonalika. Four genotypes, viz. HI 1612, MACS 6747, UP 3016 and MACS 4059 (durum) were having rAUDPC values less than 25 % of susceptible variety, Sonalika. Such genotypes showed slow progress of head blight.